Settlers, strongholds, themes. Byzantine activities to strengthen the border with Early Medieval Bulgaria, 7th–10th c. - Marinow, Kirił (Balcanica Posnaniensia. Acta et studia, 2020)
The article raises issues related to the Byzantine reconquista of the Thracian and Macedonian lands after the period of barbarian invasions on the Balkan Peninsula in the 5th–7th c. When implementing the plan to recover these areas, the authorities in Constantinople had to take into account the real threat from the Bulgarian Khanate, established north of the Haimos Mountains. Bulgarians threatened not only the success of the Byzantine venture, but they went much further south, reaching in their raids the surroundings of the imperial capital (in the southeast) or the geographical and historical lands of Macedonia (in the southwest). To remedy this, and to make their presence more real in these areas, the emperors moved there the population from Asia Minor to fulfill the existing settlement voids, embedding them in already existing or newly built fortresses and cities (as garrison units), or on arable lands (rural settlement). Another step was the creation of specific administrative units in the indicated areas, through which it was easier to administer them and effectively organize resistance against invaders from the north. Local settlers also constituted the basic military force obliged to protect these border territories. On the other hand, Thracian strongholds played the role of Byzantine outposts and bases for imperial expeditions organized against Bulgaria itself.